2018
DOI: 10.18632/oncotarget.24232
|View full text |Cite
|
Sign up to set email alerts
|

Effective screening of T cells recognizing neoantigens and construction of T-cell receptor-engineered T cells

Abstract: Neoantigens are the main targets of tumor-specific T cells reactivated by immune checkpoint-blocking antibodies or when using tumor-infiltrating T cells for adoptive therapy. While cancers often accumulate hundreds of mutations and harbor several immunogenic neoantigens, the repertoire of mutation-specific T cells in patients might be restricted. To bypass suboptimal conditions, which impede the reactivation of existing T cells or the priming of neoantigen-specific T cells in a patient, we employ T cells of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 53 publications
1
55
0
Order By: Relevance
“…Probably these two peptides bound equally to HLA-A2 and did not influence the recognition by TCR. We have previously to HLA-A was also similar between mutant and wild-type peptides) (16). On the other hand, amino acid substitutions in RFC5 and BRAP proteins occurred in P4 and P3 positions of the epitope peptides, respectively.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Probably these two peptides bound equally to HLA-A2 and did not influence the recognition by TCR. We have previously to HLA-A was also similar between mutant and wild-type peptides) (16). On the other hand, amino acid substitutions in RFC5 and BRAP proteins occurred in P4 and P3 positions of the epitope peptides, respectively.…”
Section: Discussionsupporting
confidence: 52%
“…© 2018 American Association for Cancer clincancerres.aacrjournals.org Downloaded from protocol requires only two weeks from the priming of T cells with neoantigens to the identification of neoantigen-specific TCRs (16). We previously reported that our nextgeneration sequencer-based TCR repertoire analysis is able to accurately identify V-(D)-J combinations including CDR3 sequences in various types of tumor samples (26,29,30,(35)(36)(37)(38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As summarized in Table , there are several reports in which neoantigen‐specific T cells were successfully induced. We also developed a rapid pipeline to identify TCRs recognizing neoantigens . The process takes only approximately 2 weeks.…”
Section: Neoantigen Predictionmentioning
confidence: 99%